Efficacy of Long-Term Daily Dosage of Alfuzosin 10 mg upon Sexual Function of Benign Prostatic Hypertrophy Patients: Two-Year Prospective Observational Study - Yoon, Sol; Choi, Jae Hwi; Lee, Seung Hyun; Choi, See Min; Jeh, Seong Uk; Kam, Sung Chul; Hwa, Jeong Seok; Chung, Ky Hyun; Hyun, Jae Seog (The world journal of men's health, 2014)
To identify sexual function improvement associated with alfuzosin (10 mg daily for 2 years). We enrolled 30 men with lower urinary tract symptom (LUTS) who visited Gyeongsang National University Hospital between 2010 and 2012. At first visit, urinalysis, prostate specific antigen, transrectal ultrasound, and uroflowmetry were performed. The nternational Prostate Symptom Score (IPSS), quality of life (QoL), International Index of Erectile Function (IIEF), and Male Sexual Health Questionnaire Ejaculation Function Domain (MSHQ-EjFD) questionnaires were administered, and the subjects answered the same questionnaires at 1 month, 6 months, 1 year, and 2 years of follow-up. Twelve men completed of the entire study. After administration of alfuzosin, the median IPSS at first visit, 1 month, 6 months, 1 year, and 2 years was 18.00 (interquatile range [IQR]: 14.00~29.75), 20.00 (IQR: 11.50~30.00), 15.50 (IQR: 8.50~25.25), 14.50 (IQR: 9.25~19.50), and 11.50 (IQR: 5.00~17.75), respectively, which showed an improvement. The median QoL at the same times was 4.50 (IQR: 4.00~5.00), 4.50 (IQR: 4.00~5.00), 3.00 (IQR: 2.00~4.00), 3.50 (IQR: 2.25~4.00), and 3.00 (IQR: 1.00~3.00), respectively, and also showed improvement. Likewise, the median IIEF was 36.50 (IQR: 24.50~46.75), 37.50 (IQR: 26.75~47.25), 45.50 (IQR: 35.00~59.75), 48.50 (IQR: 34.75~62.75), and 47.50 (IQR: 43.25~61.00), while the median MSHQ-EjFD was 19.00 (IQR: 12.0~24.75), 19.50 (IQR: 13.50~27.75), 23.00 (IQR: 19.25~32.25), 26.50 (IQR: 18.25~34.50), 27.00 (IQR: 21.50~32.50), respectively, with both showing improvement. After administration of alfuzosin (10 mg daily for 2 years), the IPSS, QoL, IIEF, and MSHQ-EjFD all improved significantly. This means long-term administration of 10 mg of alfuzosin daily would be effective not only for LUTS but also erectile function and ejaculation.